Are Background Measurements Able to Remove the Degeneracy between the Dark Energy Models? - Avinash Singh, Laxmikant Chaware, Arun Kumar Diwakar, Aloke Verma, Tripti Richhariya, Ekta Chandrawanshi (Mathematical Statistician and Engineering Applications, 2023)
Many dark energy models aptly describe the present-day accelerated expansion. The model is the most popular and widely used. This model presents some theoretical challenges and observational inconsistencies. There are many alternatives for this model: the barotropic fluid model, the quintessence scalar field models, the tachyon scalar field models, etc. These models potentially explain the present-day accelerated expansion and satisfy the observational data. In this study, we analyse whether the background distance measurement can be used to break this degeneracy. We find that if the present value of the dark energy equation of state is -1 (a value for cosmological constant), then all the background models show the same past evolution. Even if the equation of state deviates from , the background evolution for the different models differs only at higher redshifts. Therefore, we need high redshift observations to break the degeneracy between models. Studying the effect of the dark energy perturbation on the structure formation is also helpful for this purpose.